2022
DOI: 10.1155/2022/6721695
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compound Lactic Acid Bacteria Capsules on the Small Intestinal Bacterial Overgrowth in Patients with Depression and Diabetes: A Blinded Randomized Controlled Clinical Trial

Abstract: Objective. The objective is to explore the clinical effect of compound lactic acid bacteria capsules on the small intestinal bacterial overgrowth (SIBO) in patients with depression and diabetes. Methods. From January 2020 to January 2021, 60 SIBO patients with depression and diabetes in our hospital were selected and randomized into observation group (compound lactic acid bacteria capsules combined with escitalopram) and control group (Escitalopram) according to the odd and even numbers, 30 cases in each group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 9 publications
1
12
0
Order By: Relevance
“…It indicates that the associations of AA and LA with the drug ESCI might enhance their antidepressant-like action. In addition, these results agree with existing experimental results [23,24]. Further, the ESCI…AA interaction is found theoretically to be performing better than the drug ESCI alone and ESCI…LA couple docked in 6HIS.…”
Section: Esci…aa and 6hissupporting
confidence: 90%
See 1 more Smart Citation
“…It indicates that the associations of AA and LA with the drug ESCI might enhance their antidepressant-like action. In addition, these results agree with existing experimental results [23,24]. Further, the ESCI…AA interaction is found theoretically to be performing better than the drug ESCI alone and ESCI…LA couple docked in 6HIS.…”
Section: Esci…aa and 6hissupporting
confidence: 90%
“…The results were in support of the beneficial anti-inflammatory and anti-oxidant effects of ESCI in ulcerative colitis regardless of depressive conditions. Further, in 2022, the effect of the LA bacteria capsules on small intestinal bacterial overgrowth in patients with depression and diabetes was explored [24]. The results of this study used ESCI for depression states suggested that the compound LA bacteria capsule is a boon for patients of small intestinal bacterial overgrowth with depression and diabetes and can improve immune function and ease depression symptoms and reduce fasting plasma glucose and level of inflammatory factors.…”
Section: Introductionmentioning
confidence: 93%
“…When the intestinal microecology is out of balance, it will lead to aggravation of anxiety and depression symptoms, which counteracts on the gastrointestinal tract, causing microbiota imbalance, among which SIBO is the most common type. Consequently, it is particularly important to find a reliable and safe treatment for SIBO combined with depression [197].…”
Section: Group 10 Mental Disordersmentioning
confidence: 99%
“…LAB, including Lactobacillus and Streptococcus lactis, have shown a positive effect in terms of improving the immunity of individuals. Wei et al [108] explored the clinical effect of compound LAB capsules with Escitalopram (a medicine used to treat depression) on small intestinal bacterial overgrowth (SIBO) in patients with depression and diabetes. CD 3+ and CD +4 showed a greater increment among individuals supplemented with LAB compared to the control.…”
Section: Immunomodulatory Effects Of Labmentioning
confidence: 99%